Glycogen metabolism regulation in neurospora crassa - Bertolini, Maria C. [UNESP]; Freitas, Fernanda Z. [UNESP]; De Paula, Renato M.; Cupertino, Fernanda B. [UNESP]; Goncalves, Rodrigo D. [UNESP] (Springer Nature, 2012)
Microorganisms accumulate glycogen as carbon and energy reserves to face adverse environmental conditions during growth and development. The processes of glycogen synthesis and degradation share similarities among different microorganisms. However, the regulation of the metabolism as a whole shows differences, likely due to the environmental conditions to which they individually respond. This chapter aims to present some molecular mechanisms that regulate glycogen metabolism in the fungus Neurospora crassa. The availability of its genome sequence (Galagan et al., Nature 422:859-868, 2003) and a collection of mutant strains, each carrying a deletion in a specific ORF, allowed investigation into the role of specific proteins as regulators of glycogen metabolism to begin. Here we present some biochemical and molecular mechanisms that have already been described for this fungus, and additionally, we focused on more recent findings including the molecular basis underlying the metabolism regulation, mainly at transcriptional level.